LOCAL EFFECT OF SARSAPADI TAILA IN THE MANAGEMENT OF UNCOMPLICATED OSTEOARTHRITIS W.S.R TO SANDHIVATA: A PILOT STUDY - sharma, *Pooja; Divya, Kajaria (International Journal of Ayurveda and Pharma Research, 2019)
Osteoarthritis (degenerative joint disease) is the most common joint disorder and it mostly affects cartilage. Osteoarthritis (OA) is of two types, primary (idiopathic) and secondary. In idiopathic osteoarthritis, the most common form of the disease, no predisposing factor is apparent. Secondary OA is pathologically indistinguishable from idiopathic OA but is attributable to an underlying cause. The NSAIDs are the main drugs of choice in modern medicine which have lots of side effects and therefore are not safe for long-term therapy. According to Ayurveda OA can be correlated with Sandhivata which is mentioned by Acharya Charak as a sign and symptoms of Sandhigatavata are Shula, Shotha, Stambha, Sparsha-asahyata, Sphutana, Akunchana Prasarana Vedana. The aim of the present study was to see the local effect of Sarsapadi Taila, two times in a day for 30 days. Ingredient of Sarsapadi taila is Sarsap taila, Aadrak and Ajwain. The preparation of Taila was done as mentioned in Sharangdhar Samhita. The ratio of the three components is Kalka (AadraK+ Ajwain) one part, Sneha dravya (Sarsap taila) four parts and Drava (water) should be 16 parts. A pilot study was done in All India institute of Ayurveda hospital. In present study total 25 patients were treated with Sarsapadi Taila which was already taking modern analgesics. After the whole study results were analyzed and tapering the analgesic dose of medicine, there was mild significant changes in the condition of the patients. It is advised to Sarsapadi Taila can be used for the treatment of Sandhivata for a long time.